1998
DOI: 10.1111/j.1399-302x.1998.tb00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrarily primed polymerase chain reaction fingerprinting for the genotypic identification of mutans streptococci from humans

Abstract: Determining whether two strains of bacteria are unique, identical or clonally related depends upon comparisons of phenotypic and/or genotypic traits. Individual isolates can then be grouped according to differences or similarities among those traits. One method of genotyping strains of bacteria is commonly referred to as chromosomal DNA fingerprinting. Previously, we generated chromosomal DNA fingerprints of mutans streptococci to study the transmission of this organism within families. Here, we developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 26 publications
3
80
1
3
Order By: Relevance
“…It has been shown that the polymorphism in length of the amplified sequences (amplicons) of RAPD fingerprints obtained by AP-PCR can be used to compare bacterial strains [22][23][24], including the groups of mutans streptococci [28,29] and mitis streptococci [30]. In the present study, this application of RAPD analysis to genotyping of oral streptococci confirmed that the RAPD assay can distinguish the species S. mutans and S. sobrinus from each other.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…It has been shown that the polymorphism in length of the amplified sequences (amplicons) of RAPD fingerprints obtained by AP-PCR can be used to compare bacterial strains [22][23][24], including the groups of mutans streptococci [28,29] and mitis streptococci [30]. In the present study, this application of RAPD analysis to genotyping of oral streptococci confirmed that the RAPD assay can distinguish the species S. mutans and S. sobrinus from each other.…”
Section: Discussionsupporting
confidence: 54%
“…As the RAPD profiles have only a small number of bands and, consequently, are much easier to read than the corresponding REA patterns, they should be considered helpful for epidemiological and transmission studies of mutans and other oral streptococci, as already shown with P. gingivalis [27] and suggested for mutans streptococci [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of oral bacteria by AP-PCR or DNA fingerprinting has become well-accepted (Saarela et al, 1996;Li and Caufield, 1998;Gronroos and Alaluusua, 2000;Li et al, 2001;Toi et al, 2003;Ersin et al, 2004;Klein et al, 2004;Liu et al, 2004;Napimoga et al, 2004;Nascimento et al, 2004;Kamiya et al, 2005;Li et al, 2005;Cogulu et al, 2006;Liu et al, 2007;Hames-Kocabas et al, 2008). Moreover, AP-PCR has been shown to have good discriminating ability for mutans streptococci differentiation (Saarela et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported transmission between family members, such as spouse-spouse, father-child, and sibling-sibling (Saarela et al, 1993;Li and Caufield, 1998;Redmo Emanuelsson and Wang, 1998;Kozai et al, 1999;Emanuelsson and Thornqvist, 2000;van Loveren et al, 2000;Redmo Emanuelsson and Thornqvist, 2001;Nie et al, 2002;Tedjosasongko and Kozai, 2002;Ersin et al, 2004;Hames-Kocabas et al, 2008). Although there have been three reports of transmission between unrelated young infants in nursery schools in China, Brazil, and Japan (Mattos-Graner et al, 2001;Tedjosasongko and Kozai, 2002;Liu et al, 2007), these children ranged in age from 2 mos to 4 yrs, when salivary transfer is more likely than in older children.…”
Section: Discussionmentioning
confidence: 99%